The Criminalization Of Illicit Enrichment in Combating Corruption in Indonesia - Dianita,; Pujiyono,; Sutanti, Rahmi Dwi (Mahadi: Indonesia Journal of Law, 2023)
Despite Indonesia's ratification of the United Nations Convention against Corruption, 2003 (UNCAC, 2003), there are still some norms that have not been adequately accommodated by national anti-corruption laws, particularly concerning illicit enrichment. This legal study aims to examine the practical implementation of illicit enrichment as a corruption offense in Indonesia and propose the criminalization of illicit enrichment as a future corruption offense. The research methodology employed is normative juridical, which involves analyzing secondary data, with a focus on literature reviews and relevant legislation. The research findings and discussions indicate that the practice of illicit enrichment has been increasingly prevalent, as evidenced by cases involving defendants Bahasyim Assifie and Dhana Widyatmika, who were charged under different articles, namely Article 12 of the Anti-Corruption Law and Article 3 of the Anti-Money Laundering Law, which differ from the essence of illicit enrichment as outlined in UNCAC, 2003. Considering the enforcement practices, it is imperative to criminalize the act of unlawful enrichment or illicit enrichment through the revision of the Anti-Corruption Law or the Criminal Code.